TINGKAT PENGETAHUAN DAN KETERAMPILAN PETANI PADA USAHA TANI NILAM DALAM UPAYA PENINGKATAN PENDAPATAN DI DESA SAMBAHULE KECAMATAN BAITO KABUPATEN KONAWE SELATAN - Muh Haerul Candra; Musadar Musadar; Putu Arimbawa (Jurnal Ilmiah Penyuluhan dan Pengembangan Masyarakat, 2022)
This studies aims to: (1) determine the level of knowledge and skills of farmers in managing patchouli farming in Sambahule Village, Baito District, South Konawe Regency, (2) determine the level of farmers' income in patchouli farming in Sambahule Village, Baito District, South Konawe Regency, (3) knowing the relationship between the level of knowledge and skills of farmers with the level of income of farmers in patchouli farming. This research was conducted in Sambahule Village, Baito District, Konawe Selatan Regency which was carried out from September 2021 to January 2022 with a total of 45 respondents who were determined using simple random sampling technique. Data analysis used descriptive statistical methods (class interval) and nonparametric inferential (spearman rank). with the help of SPSS 16 software. The results of this study indicate that (1) the level of knowledge and skills of farmers in managing patchouli farming is in good category (2) farmers' income in patchouli farming is in low category (3) there is a significant relationship between the level of knowledge and skills of farmers with the level of farmers' income in patchouli farming.